2014
DOI: 10.1681/asn.2013121270
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of p53 in the Proximal Tubule Prevents Ischemic Renal Injury

Abstract: The contribution of p53 to kidney dysfunction, inflammation, and tubular cell death, hallmark features of ischemic renal injury (IRI), remains undefined. Here, we studied the role of proximal tubule cell (PTC)-specific p53 activation on the short-and long-term consequences of renal ischemia/reperfusion injury in mice. After IRI, mice with PTC-specific deletion of p53 (p53 knockout [KO]) had diminished whole-kidney expression levels of p53 and its target genes, improved renal function, which was shown by decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
101
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 47 publications
6
101
1
Order By: Relevance
“…[11] showed an administration of pifithrin-α in a single dose at 3 and 14 days after unilateral IRI in mice resulted in diminished cell cycle arrest and fibrosis. In a recent report, Yuan et al [20] also showed that the specific deletion of p53 in the proximal tubule cells attenuated cell cycle arrest and prevented kidney fibrosis [20]. Therefore, in our study, significantly elevated levels of p53 and p21 after AKI in CKD mice compared to AKI in control mice is thought to be partially responsible for progression of fibrosis and inadequate recovery of renal function.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…[11] showed an administration of pifithrin-α in a single dose at 3 and 14 days after unilateral IRI in mice resulted in diminished cell cycle arrest and fibrosis. In a recent report, Yuan et al [20] also showed that the specific deletion of p53 in the proximal tubule cells attenuated cell cycle arrest and prevented kidney fibrosis [20]. Therefore, in our study, significantly elevated levels of p53 and p21 after AKI in CKD mice compared to AKI in control mice is thought to be partially responsible for progression of fibrosis and inadequate recovery of renal function.…”
Section: Discussionsupporting
confidence: 58%
“…The existence of a strong association between p53 and fibrosis has been demonstrated previously. Several studies have shown that the prolonged induction of p21 and p53 is detrimental to kidney fibrosis through continued cell cycle arrest and thus blocking p53 results in the release of arrest and prevention of fibrosis [14, 20]. Yang et al .…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment analysis of these targets showed the over-representation of processes associated with the first stages of kidney damage and repair by stem cell administration, such as the cell adhesion molecules and MAPK signaling. 38 Interestingly, the Wnt signaling pathway, 39 ECM remodeling, 40 and the p53 pathway 41 were also present among the significant biologic processes identified (data not shown). These processes are usually associated with relevant stages in the transition from acute to chronic injury, such as vascular failure, interstitial fibrosis, and glomerulosclerosis development.…”
Section: Discussionmentioning
confidence: 97%
“…These processes are usually associated with relevant stages in the transition from acute to chronic injury, such as vascular failure, interstitial fibrosis, and glomerulosclerosis development. [38][39][40][41] By selecting in this set, only genes not reverted in EV-Dsh treatment with respect to AKI, 165 genes resulted as the possible miRNA targets. GO enrichment analysis of these genes showed that EV-Dshtreated mice overexpressed genes associated with processes related with the progression of kidney damage, such as the Wnt pathway, p53 signaling, ECM remodeling, and focal adhesion processes, like the untreated AKI.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN regulates p53 protein levels and transcriptional activity through both phosphatase dependent and independent mechanisms. A crucial role of p53 in tubules damaged by ischemia reperfusion has been reported by the authors' group and others, [12][13][14] and a role of p53 in the HIF-1/miR-687/PTEN signaling pathway is an important issue to be pursued.…”
mentioning
confidence: 86%